Rational therapy of osteoarthritis - E G Zotkin (Научно-практическая ревматология, 2005)
Brief information about modem osteoarthritis treatment with simple analgesics, NSAIDs and chondroprotective drugs is presented. Results of a clinical study of ARTRA in combination with diclofenac (31 pts) comparing with diclofenac only (31 pts) for the treatment of knee osteoarthritis ofll-lll stage are discussed. ARTRA was administered 2 capsules a day during a months and than 1 capsule a day during 5 months. A mean therapeutic dose of diclofenac was given to all pts. ARTRA with diclofenac was more effectively than diclofenac monotherapy improved WOMAC functional index and suppressed pain on visual analog scale and WOMAC. ARTRA was well tolerated.